Association between immunoglobulin heavy-chain variable region mutational status and isolated favorable baseline genomic aberrations in chronic lymphocytic leukemia. Issue 1 (2nd January 2018) - Sandoval-Sus, Jose D.; Chavez, Julio C.; Dalia, Samir; Naqvi, Syeda Mahrukh Hussnain; Talati, Chetasi; Nodzon, Lisa; Kharfan-Dabaja, Mohamed A.; Pinilla-Ibarz, Javier
Abstract: Immunoglobulin heavy-chain variable region ( IGHV ) mutational status and karyotype abnormalities are important prognostic factors in chronic lymphocytic leukemia (CLL). The goal was to assess the impact of IGHV in CLL patients with isolated favorable genetic aberrations (del13q, trisomy 12, or negative fluorescence in situ hybridization [FISH]). We studied 273 CLL patients with both IGHV mutational status and cytogenetic information: 145 with isolated del13q 49 with sole trisomy 12 and 79 with negative FISH. After a median follow-up of 7.8 years, patients with del13q-unmutated IGHV had a shorter time to first treatment (TFT) (2.98 vs. 17.44 years; p  < .001) and shorter overall survival (10.45 years vs. not reached; p  = .0026). Patients with negative FISH-unmutated IGHV had shorter TFT ( p  = .02) (3.10 vs. 9.75 years, p  = .053). IGHV status did not influence clinical outcomes in trisomy 12 CLL. In conclusion, IGHV mutational status shows prognostic impact in CLL patients with good prognosis genomic features.